Potential clinical impact of T-cell lymphocyte kinetics monitoring in patients with B cell precursors acute lymphoblastic leukemia treated with blinatumomab: a single-center experience - Duminuco, Andrea; Markovic, Uros; Parrinello, Nunziatina Laura; Lo Nigro, Luca; Mauro, Elisa; Vetro, Calogero; Parisi, Marina; Maugeri, Cinzia; Fiumara, Paolo Fabio; Milone, Giuseppe; Romano, Alessandra; Di Raimondo, Francesco; et al. (Frontiers in Immunology, 2023)
Blinatumomab is a bispecific anti-CD3 and anti-CD19 antibody that acts as a T-cell engager: by binding CD19+ lymphoblasts, blinatumomab recruits cytotoxic CD3+ T-lymphocytes to target the cancer cells. Here we describe seven different patients affected by B-cell precursor acute lymphoblastic leukemia (Bcp-ALL) and treated with blinatumomab, on which we evaluated the potential association between the amount of different T-cells subsets and deep molecular response after the first cycle, identified as a complete remission in the absence of minimal residual disease (CR/MRD). The immune-system effector cells studied were CD3+, CD4+ effector memory (T4-EM), CD8+ effector memory (T8-EM), and T-regulatory (T-reg) lymphocytes, and myeloid-derived suppressor cells (MDSC). Measurements were performed in the peripheral blood using flow cytometry of the peripheral blood at baseline and after the first cycle of blinatumomab. The first results show that patients with a higher proportion of baseline T-lymphocytes achieved MRD negativity more frequently with no statistically significant difference (p=0.06) and without differences in the subpopulation count following the first treatment. These extremely preliminary data could potentially pave the way for future studies, including larger and less heterogeneous cohorts, in order to assess the T-cell kinetics in a specific set of patients with potential synergy effects in targeting myeloid-derived suppressor cells (MDSC), commonly known to have an immune evasion mechanism in Bcp-ALL.